Fundamentals of Multinational Finance - MOFFETT, M.H (Pearson Education Limited, 2024)
For undergraduate courses in International Financial Management, International Business Finance, or International Finance. Real-world examples introduce readers to global financial management strategy Fundamentals of Multinational Finance helps prepare tomorrow's business leaders to comprehend global markets and lead organizations through a constantly changing global environment. Via illuminating case studies and real-world examples, readers are introduce